Exploring the genre of academic oral presentations: a critical review - Maktiar Singh, Kuldip Kaur; Mohamad Ali, Afida (Australian International Academic Centre, 2018)
Conducting Academic Oral Presentation (AOP) is an endeavour for undergraduates although it is a key academic genre for undergraduates. Despite its importance, there remains a paucity of studies on this oral genre in the Malaysian context as shown in the body of the literature. This paper provides a critical review of the literature on AOP and discusses the advantages and limitations of the previous studies to date on this oral genre. The literature shows most studies that adopt the genre analysis approach typically analyse only one section of the oral genre. These studies have not examined the AOP rhetorical structure in totality. Moreover, studies on multimodal analysis of AOP comparing the verbal and non-verbal modes are limited. Only few studies have attempted to examine the juxtaposition of the moves, linguistic elements and the visuals. AOPs are ubiquitous for the students across various courses and disciplines in the university and past studies have also compared the differences between disciplines (Zappa-Hollman, 2007; Morita, 2000).Thus, realizing the importance of AOP, clearly there is a necessity to conduct more research in this area in the local context.